2016
DOI: 10.5964/ejop.v12i3.1107
|View full text |Cite
|
Sign up to set email alerts
|

Clowning in health care settings: The point of view of adults

Abstract: Within the past decade, there has been a surge of interest in investigating the effects of clown intervention in a large variety of clinical settings. Many studies have focused on the effects of clown intervention on children. However, few studies have investigated clowning effects on adults. This paper presents an overview of the concept of medical clowning followed by a literature review conducted on the empirical studies drawn from three data bases (PubMed, PsycINFO, and Google Scholar), with the aim of map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 27 publications
1
52
0
10
Order By: Relevance
“…To sum up, previous research has indicated that medical clowns help in providing effective treatment by bringing out positive emotions in hospitalized patients [1]. Our research ndings support the notion that a sense of humor aids in predicting personal outcomes for medical clowns.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…To sum up, previous research has indicated that medical clowns help in providing effective treatment by bringing out positive emotions in hospitalized patients [1]. Our research ndings support the notion that a sense of humor aids in predicting personal outcomes for medical clowns.…”
Section: Resultssupporting
confidence: 84%
“…Actions such as these would be particularly effective during their early stages in the profession Moreover, humor can be learned, trained, or otherwise leveraged for organizational advantage [28]. Finally, although medical clown interventions have been shown to mitigate the negative effects of hospitalization and have a positive impact on both patients and medical staff [1,2,4 ], it seems that we need a better understanding of clowns' personality in order to integrate them in the healthcare delivery system. In their typical work experience, the medical clown performs alone and, in some cases, in a non-supportive environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Original research on this topic was first published in 2005 [19], when a group of Italian researchers conducted a randomized controlled trial at Meyer Children's Hospital in Florence [14]. The researchers found that the group of children accompanied by clowns and a parent experienced significantly less anxiety in the operating theater, as measured by the modified-Yale Preoperative Anxiety Scale (m-YPAS), compared to the control group, who only had the company of a parent.…”
Section: The Efficacy Of Clown Interventions In Hospital Settingsmentioning
confidence: 99%